CARA MUDAH MEMBANGUN APLIKASI RENTAL MOBIL DAN FORM PEMESANAN BERBASIS WEBSITE - Arisantoso; Nauli, Rahmad; Pratama, Sandi Pramudya; Abdulloh, Endang (JI-Tech, 2023)
PT Perkasa Satria Nusantara was established on September 12 2013 and stipulated by Decree of the Minister of Law and Human Rights of the Republic of Indonesia Number: AHU-65375.AH.01.01. 2013 on December 13 2013. PT Perkasa Satria Nusantara was established as a form of concern and service to customers, especially in the field of security, creating a sense of security and comfort for every customer. Starting from services in the field of Security Service Providers (SATPAM), PT. Perkasa Satria Nusantara serves CCTV Sales, Installation, Repair and Maintenance, IT Support & Web Management. PT. Perkasa Satria Nusantara also provides Car and Driver Rental Services. With the design of a Website-based Car Rental Order Information System that makes it easier to manage data from the admin side, makes it easier to receive orders from the driver's side, makes it easier to order from the customer side so that it is more efficient and flexible in ordering car rentals in Indonesia. PT. Mighty Satria Nusantara. The research method is through literature studies and the concept of System Development Life Cycle with one of the Extreme Programming (XP) models and flow charts using the Unified Modeling Language (UML) design.